Chronic Lead Exposure and Mixed Factors of Gender×Age×Brain Regions Interactions on Dendrite Growth, Spine Maturity and NDR Kinase - Du, Yang; Ge, Meng-Meng; Xue, Weizhen; Yang, Qian-Qian; Wang, Shuang; Xu, Yi; Wang, Hui-Li (PloS one, 2015)
NDR1/2 kinase is essential in dendrite morphology and spine formation, which is regulated by cellular Ca2+. Lead (Pb) is a potent blocker of L-type calcium channel and our recent work showed Pb exposure impairs dendritic spine outgrowth in hippocampal neurons in rats. But the sensitivity of Pb-induced spine maturity with mixed factors (gender×age×brain regions) remains unknown. This study aimed to systematically investigate the effect of Pb exposure on spine maturity in rat brain with three factors (gender×age×brain regions), as well as the NDR1/2 kinase expression. Sprague-Dawley rats were exposed to Pb from parturition to postnatal day 30, 60, 90, respectively. Golgi-Cox staining was used to examine spine maturity. Western blot assay was applied to measure protein expression and real-time fluorescence quantitative PCR assay was used to examine mRNA levels. The results showed chronic Pb exposure significantly decreased dendritic length and impaired spine maturity in both rat hippocampus and medial prefrontal cortex. The impairment of dendritic length induced by Pb exposure tended to adolescence > adulthood, hippocampus > medial prefrontal cortex and female > male. Pb exposure induced significant damage in spine maturity during adolescence and early adult while little damage during adult in male rat brain and female medial prefrontal cortex. Besides, there was sustained impairment from adolescence to adulthood in female hippocampus. Interestingly, impairment of spine maturity followed by Pb exposure was correlated with NDR1/2 kinase. The reduction of NDR1/2 kinase protein expression after Pb exposure was similar to the result of spine maturity. In addition, NDR2 and their substrate Rabin3 mRNA levels were significantly decreased by Pb exposure in developmental rat brain. Taken together, Pb exposure impaired dendrite growth and maturity which was subject to gender×age×brain regions effects and related to NDR1/2 signal expression.